Natural rate chimera and bond pricing reality - Claus Brand; Gavin W Goy; Wolfgang Lemke (ZBW - Leibniz Information Centre for Economics, 2020)
Incorporating arbitrage-free term-structure dynamics into a semi-structural macro-model, we jointly estimate the real equilibrium interest rate (r*), trend inflation, and term premia for the United States and the euro area, using a Bayesian approach. The natural real rate and trend inflation are cornerstones determining equilibrium yields across maturities and macroeconomic trends. Taking into account the secular decline in equilibrium rates, term premia exhibit cyclical behavior over the business cycle, rather than the commonly reported trend. Our estimates suggest a fall in r* from a pre-crisis level of about 3% to around zero, but estimates are subject to sizeable uncertainty. Including survey expectations can lift r* estimates for recent quarters by a margin.
Keywords: C11; C32; E43; G12; E44; E52; 330; Natural rate of interest; r*; equilibrium real rate; arbitrage-free Nelson-Siegel term structure model; term premia; unobserved components; Bayesian estimation